Effects of Moringa oleifera on working memory: an experimental study with memory-impaired Wistar rats tested in radial arm maze - Sadia Afrin; Ahmed Hossain; Shelina Begum (BMC Research Notes, 2022)
Abstract Objective Memory impairment is a serious problem that has a significant negative impact on survival and quality of life. When used for a long time, drugs used to treat memory loss become less effective and have more side effects, making therapy more difficult. Different medicinal plants are now being highlighted because of their valuable applications and low risk of adverse effects. Moringa oleifera is one of these plants that has gained much attention due to its diverse biological functions. The study aimed to determine the effects of Moringa oleifera on working memory in memory-impaired Wistar rats. Results For this experimental study, 30 male Wistar rats having 150–250 g bodyweight were divided equally into three groups: Group-I/normal memory group (treated with oral normal saline 5 ml/kg body weight), Group-II/memory-impaired group (induced by intraperitoneal ketamine 15 mg/kg body weight), and Group-III/experimental group (treated with oral Moringa oleifera 200 mg/kg bodyweight and intraperitoneal ketamine 15 mg/kg body weight). The experimental group showed significantly fewer working memory errors than the memory-impaired group. The experimental group also provides the lowest variability of WMEs among groups. Thus, the study concludes that M. oleifera can prevent ketamine-induced memory impairment in Wistar rats.